Ultrasound‐assisted minimally invasive technique for tissue collection from bovine mammary glands - Alysia L. Vang; Waneska S. Frizzarini; Haylee H. Webster; Thiago O. Cunha; Kathryn M. Nelson; Joao R. R. Dorea; Laura L. Hernandez (Veterinary Medicine and Science)
Abstract Background and Aims The objective of this case report was to describe an ultrasound‐guided, minimally invasive method for longitudinal mammary gland tissue collection from the bovine species. Materials and Methods Biopsies were performed on 14 8‐week‐old calves and 113 10‐week‐old calves. A subset of 36 animals had repeated mammary gland biopsies through the first lactation. Mammary gland biopsies were performed using a disposable biopsy punch. The technique was also performed on multiparous cows on other independent research trials. Results One‐hundred and thirteen animals healed from the 10‐week biopsies with no complications. Of the 36 animals that received repeated biopsies, one developed mastitis due to premature suture removal and one had recurring mastitis in all quarters. Thirty‐three animals underwent all biopsies during gestation. Thirty of the original 36 are currently in lactation and still undergoing repeated biopsies. The method has also been successfully replicated on multiparous cows in separate studies. Discussion and Conclusion The described technique is a safe, reliable method for cattle mammary gland biopsies beginning at eight weeks of age and can be utilized to obtain repeated tissue collection from individual animals. The technique is also straightforward to perform and utilizes simple tools while providing acceptable amounts of tissue for most applications, with low risk for infection and long‐term tissue damage.